On the origin of the family - Marco Francesconi; Christian Ghiglino; Motty Perry (Institute for the Study of Labor (IZA), 2009)
This paper presents an overlapping generations model to explain why humans live in families rather than in other pair groupings. Since most non-human species are not familial, something special must be behind the family. It is shown that the two necessary features that explain the origin of the family are given by uncertain paternity and overlapping cohorts of dependent children. With such two features built into our model, and under the assumption that individuals care only for the propagation of their own genes, our analysis indicates that fidelity families dominate promiscuous pair bonding, in the sense that they can achieve greater survivorship and enhanced genetic fitness. The explanation lies in the free riding behavior that characterizes the interactions between competing fathers in the same promiscuous pair grouping. Kin ties could also be related to the emergence of the family. When we consider a kinship system in which an adult male transfers resources not just to his offspring but also to his younger siblings, we find that kin ties never emerge as an equilibrium outcome in a promiscuous environment. In a fidelity family environment, instead, kinship can occur in equilibrium and, when it does, it is efficiency enhancing in terms of greater survivorship and fitness. The model can also be used to shed light on the issue as to why virtually all major world religions are centered around the importance of the family.
Keywords: C72; D01; D10; J12; Z13; 330; Fatherhood uncertainty; free riding; kinship systems; religion; overlapping generations; divorce and blended families; Familienökonomik; Väter; Risiko; Trittbrettfahrerverhalten; Familiensoziologie; Overlapping Generations; Religion; Theorie